Association between HIV stigma and antiretroviral therapy adherence among adults living with HIV: baseline findings from the HPTN 071 (PopART) trial in Zambia and South Africa. Issue 10 (26th August 2020) - Jones, Harriet S.; Floyd, Sian; Stangl, Anne; Bond, Virginia; Hoddinott, Graeme; Pliakas, Triantafyllos; Bwalya, Justin; Mandla, Nomtha; Moore, Ayana; Donnell, Deborah; Bock, Peter; Fidler, Sarah; et al.
Abstract: Objectives: Adherence to antiretroviral therapy (ART) leads to viral suppression for people living with HIV (PLHIV) and is critical for both individual health and reducing onward HIV transmission. HIV stigma is a risk factor that can undermine adherence. We explored the association between HIV stigma and self‐reported ART adherence among PLHIV in 21 communities in the HPTN 071 (PopART) trial in Zambia and the Western Cape of South Africa. Methods: We conducted a cross‐sectional analysis of baseline data collected between 2013 and 2015, before the roll‐out of trial interventions. Questionnaires were conducted, and consenting participants provided a blood sample for HIV testing. Poor adherence was defined as self‐report of not currently taking ART, missing pills over the previous 7 days or stopping treatment in the previous 12 months. Stigma was categorised into three domains: community, health setting and internalised stigma. Multivariable logistic regression was used for analysis. Results: Among 2020 PLHIV self‐reporting ever taking ART, 1888 (93%) were included in multivariable analysis. Poor ART adherence was reported by 15.8% ( n = 320) of participants, and 25.7% ( n = 519) reported experiencing community stigma, 21.5% ( n = 434) internalised stigma, and 5.7% ( n = 152) health setting stigma. PLHIV who self‐reported previous experiences of community and internalised stigma more commonly reported poor ART adherence than those who did not (aOR 1.63, 95% CI 1.21 −2.19, P = 0.001 and aOR 1.31, 95% CI 0.96–1.79, P = 0.09). Conclusions: HIV stigma was associated with poor ART adherence. Roll‐out of universal treatment will see an increasingly high proportion of PLHIV initiated on ART. Addressing HIV stigma could make an important contribution to supporting lifelong ART adherence. Abstract : Objectifs: L'adhésion à la thérapie antirétrovirale (ART) conduit à la suppression virale pour les personnes vivant avec le VIH (PVVIH) et est essentielle à la fois pour la santé individuelle et pour réduire la transmission du VIH. La stigmatisation du VIH est un facteur de risque qui peut compromettre l'adhésion. Nous avons exploré l'association entre la stigmatisation du VIH et l'adhésion autodéclarée à l'ART chez les PVVIH dans 21 communautés dans l'essai HPTN 071 (PopART) en Zambie et dans le Western Cape en Afrique du Sud. Méthodes: Nous avons effectué une analyse transversale des données de base collectées entre 2013‐2015, avant le déploiement des interventions d'essai. Des questionnaires ont été réalisés et les participants consentants ont fourni un échantillon de sang pour le dépistage du VIH. Une mauvaise adhésion a été définie comme l'autodéclaration de ne pas prendre actuellement l'ART, d'omettre des comprimés au cours des 7 jours précédents ou d'arrêter le traitement au cours des 12 mois précédents. La stigmatisation a été classée en trois domaines: communautaire, en milieu de santé et stigmatisation intériorisée. Une régression logistique multivariée a été utilisée pour l'analyse. Résultats: Parmi les 2.020 PVVIH autodéclarant avoir déjà pris un ART, 1.888 (93%) ont été inclus dans l'analyse multivariée. Une mauvaise adhésion à l'ART a été signalée par 15, 8% ( n = 320) des participants, 25, 7% ( n = 519) ont déclaré avoir subi une stigmatisation communautaire, 21, 5% ( n = 434) une stigmatisation internalisée et 5, 7% ( n = 152) une stigmatisation en milieu de santé. Les PVVIH qui ont auto‐déclaré des expériences antérieures de stigmatisation communautaire et intériorisée ont plus souvent rapporté une mauvaise adhésion à l'ART que ceux qui ne l'ont pas fait (aOR 1, 63 ; IC95%: 1, 21–2, 19 ; P = 0, 001 et aOR 1, 31 ; IC95%: 0, 96–1, 79 ; P = 0, 09). Conclusions: La stigmatisation du VIH était associée à une mauvaise adhésion à l'ART. Le déploiement du traitement universel verra une proportion de plus en plus élevée de PVVIH initiées à l'ART. Lutter contre la stigmatisation du VIH pourrait apporter une contribution importante au soutien de l'adhésion à l'ART au cours de la vie. Numéro d'essai clinique: NCT01900977